Neuropsychology, social cognition and global functioning among bipolar, schizophrenic patients and healthy controls: preliminary data - Caletti, Elisabetta; Paoli, Riccardo Augusto; Fiorentini, Alessio; Cigliobianco, Michela; Zugno, Elisa; Serati, Marta; Orsenigo, Giulia; Grillo, Paolo; Consonni, Dario; Zago, Stefano; Caldiroli, Alice; Prunas, Cecilia; et al. (Frontiers in Human Neuroscience, 2013)
This study aimed to determine the extent of impairment in social and non-social cognitive domains in an ecological context comparing bipolar (BD), schizophrenic patients (SKZ) and healthy controls (HC). The sample was enrolled at the Department of Psychiatry of Policlinico Hospital, University of Milan, it includes stabilized schizophrenic patients (n = 30), euthymic bipolar patients (n = 18) and healthy controls (n = 18). Patients and controls completed psychiatric assessment rating scales, the Brief Assessment of Cognition in Schizophrenia (BACS) and the Executive and Social Cognition Battery (ESCB) that contains both ecological tests of executive function and social cognition, in order to better detect cognitive deficits in patients with normal results in standard executive batteries. The three groups differed significantly for gender and substance abuse, however the differences did not influence the results. Bipolar patients showed less impairment on cognitive performance compared to schizophrenic patients, even in “ecological” tests that mimic real life scenarios. In particular, BD performed better than SKZ in verbal memory (p